An IoT based baby monitoring system - Hiew, Kuet Shang (2019)
The number of working mothers has greatly increased compared to the past few decades. Subsequently, baby care during daily life has become a challenge to many families. Thus, most of parents used to send their babies to grandparents’ house or baby care-house to take care of their babies. However, the parents cannot continuously monitor their babies’ conditions either in normal or abnormal situations. Therefore, this project proposes an efficient and low-cost Internet of Things (IoT) based system for baby monitoring in real time which can play a key role in providing better baby care while parents are away from their babies. In system design, NodeMCU Wi-Fi Controller Board is exploited as the main microcontroller to gather the data read by sensors and upload to the AdaFruit MQTT server. The proposed system exploits sensors to monitor baby’s vital parameters such as surrounding temperature, moisture, and crying. The sensors used in this project are KY-038 sound sensor and DHT22 temperature and humidity sensor. Proteus software is used to check the connection of the circuit and Arduino IDE is used to check errors on codes and compilation of the code into the microcontroller. Nx Siemens software is used for designing the baby cradle. Red meranti wood is used as the material for the baby cradle. For the building of baby cradle, woods are carefully cut and handled using the tools and machines available in UMP to ensure safety. The system architecture consists of a baby cradle that will automatically swing using a motor when the baby cries. Parents can also monitor their babies’ condition through an external web camera and switch on the lullaby toy located on the baby cradle remotely via the MQTT server to entertain the baby. The proposed system prototype is being fabricated and tested to prove its effectiveness in terms of cost, simplicity, and ensure safety operation to enable the baby-parenting anywhere and anytime through the network. Finally, the baby monitoring system is proven working for monitoring the baby condition and surrounding temperature on the built prototype.